Efektifitas Terapi Oksigen Terhadap Downes Score pada Pasien Asfiksia Neonatus di Ruang Perinatologi - Nurviyanti Nurviyanti; Sri Suparti (Faletehan Health Journal, 2021)
Asphyxia is a high risk for newborns since it causes death or serious illness. Newborns with asphyxia are treated with oxygen therapy to avoid respiratory distress. The degree of respiratory distress is analyzed by using Downes score. This research aimed to find out the effectiveness of oxygen therapy on Downes score of neonatal asphyxia patients in perinatology room. It was a descriptive quantitative research with analytical observation and prospective approach. 25 patients as sample were taken by accidental sampling technique. The research instrument used was the Downes score observation sheet. The data were collected from moderate to severe asphyxia infants by assessing the Downes score before and after oxygen therapy and analyzed by Wilcoxon test. The results showed largery type of asphyxia occurred was the moderate one (88%) and the respondents got nasal oxygen therapy (64%). The mean score and the standard deviation of the pre-oxygen therapy Downe Score was 3.20±2.041 and the post-therapy was 1.04±1.881. The data analysis by Wilcoxon test showed the Z-score was -4.173 and the significance level was 0.000 (p<0.05). To conclude, there is a Downes score decrease of asphyxia newborns who get oxygen therapy.